Environmental implications of soil remediation using the Fenton process - Villa, Ricardo D. [UNESP]; Trovo, Alam G. [UNESP]; Nogueira, Raquel Fernandes Pupo [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
This work evaluates some collateral effects caused by the application of the Fenton process to 1,1-bis(4-chlorophenyl)-2,2,2-trichloroethane (DDT) and diesel degradation in soil. While about 80% of the diesel and 75% of the DDT present in the soil were degraded in a slurry system, the dissolved organic carbon (DOC) in the slurry filtrate increased from 80 to 880 mg l(-1) after 64 h of reaction and the DDT concentration increased from 12 to 50 mu g l(-1). Experiments of diesel degradation conducted on silica evidenced that soluble compounds were also formed during diesel oxidation. Furthermore, significant increase in metal concentrations was also observed in the slurry filtrate after the Fenton treatment when compared to the control experiment leading to excessive concentrations of Cr, Ni, Cu and Mn according to the limits imposed for water. Moreover, 80% of the organic matter naturally present in the soil was degraded and a drastic volatilization of DDT and 2,2-bis(4-chlorophenyl)-1,1-dichloroethylene was observed. Despite the high percentages of diesel and DDT degradation in soil, the potential overall benefits of its application must be evaluated beforehand taking into account the metal and target compounds dissolution and the volatilization of contaminants when the process is applied. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: air contamination; DDT; diesel; in situ chemical oxidation; metals; organic matter